THE BENEFITS OF ERGONOMY IN THE WORK ENVIRONMENT: A BIBLIOGRAPHICAL STUDY - César Oliveira Corredeira, Rodrigo; Capita Quarto, Lucas; Maria da Fonseca Souza, Sônia; Aparecida Amiti Fabri, Karol; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
Ergonomics is the science that seeks to adjust the conditions of the working environment to the individualities of the worker, providing comfortable, safe and productive working conditions in the exercise of their function. According to experts, ergonomic procedures, when applied efficiently, contribute to the reduction of fatigue and make efficient procedures to ensure the integrity of the physical and mental health of individuals in a given work environment. In organizations, ergonomics can be applied through work gymnastics, regular intervals and task rotation, as well as adapting the work environment according to the employee's function and workload. In view of the above, this article aims to present the benefits that Ergonomics, when well applied, can offer employees in the work environment, demonstrating their importance and their contribution in the daily workday. The present research is a bibliographic study based on publications about the subject. Thus, it is concluded that ergonomic practices and knowledge allow the work to be better sized, favoring and contributing to its effectiveness, while allowing people to develop their activities in conditions much more favorable to their health and well-being.